irreversibility: A Python Package for Assessing and Manipulating the Time Irreversibility of Real-World Time Series - Zanin, Massimiliano (Entropy (Basel, Switzerland), 2025)
Time irreversibility refers to the property of some dynamical systems and time series of being statistically different when observed backward in time. While the theoretical foundations of irreversibility date back to the origin of statistical physics, the analysis of such property in real-world time series has only recently gained momentum. We present irreversibility, an open-source Python (version ≥ 3.11) package aimed at providing a large set of irreversibility metrics and tests and at facilitating their use. Besides the tests themselves, it includes a set of utilities, like functions to downsample and manipulate the time series, and to optimise the parameters of the metrics. By providing a unified software package, irreversibility simplifies the analysis of real data, allowing the researcher to compare multiple tests and obtain a better and more reproducible view of the underlying system. In this contribution we explore the features of the package and provide examples of its use.